Soft Tissue Management and Prosthetic Rehabilitation in a Tongue Cancer Patient - Umberto Romeo; Marco Lollobrigida; Gaspare Palaia; Domenica Laurito; Riccardo Cugnetto; Alberto De Biase (Case Reports in Dentistry)
One major challenge in treating head and neck oncologic patients is to achieve an acceptable recovery of physiologic functions compatible with the complete tumor excision. However, after tumor resection, some patients present a surgically altered anatomy incompatible with prosthetic rehabilitation, unless some soft tissue correction is carried out. The aim of the present study is to describe the overall mandibular prosthetic rehabilitation of a postoncologic patient focusing on the possibility of soft tissue correction as a part of the treatment. A 72-year-old woman, who undergone a hemiglossectomy for squamous cell carcinoma several years before, was referred to our department needing a new prosthesis. The patient presented partial mandibular edentulism, defects in tongue mobility, and a bridge of scar tissue connecting one side of the tongue to the alveolar ridge. A diode laser (980 nm) was used to remove the fibrous scar tissue. After reestablishing a proper vestibular depth and soft tissue morphology, two implants were placed in the interforaminal region of the mandible to support an overdenture.